DEVELOPMENT OF HYBRID LEARNING APPLICATION MODEL FOR LECTURERS STUDY PROGRAM DOCTORS OF POSTGRADUATE EDUCATION TECHNOLOGY OF JAKARTA STATE UNIVERSITY - Suyitno Muslim; Jhoni Lagun Siang; Aniesa Puspa Arum (Peneliti.net, 2019)
Purpose of this study is the development of the application of hybrid learning learning at Postgraduate State University of Jakarta. The targets in this study were lecturers who took courses in the UNJ Education Technology doctoral program. Considering this research is in the form of developing an online learning system, the research method used is research and development (R&D). the results of this study conclude as follows: 1) Readiness of students in implementing hybrid learning has met. The analysis shows that 3% is very high, 41% is high, 34% is moderate, 16% is low, and 6% is very low. 2) Lecturer readiness in implementing hybrid learning has fulfilled. From the results of the analysis showed as much as 14% Very High, 29% High, 57% Moderate, 0% Low, and 0% Very Low. 3) Readiness of facilities and infrastructure as well as policies on implementinglearning hybrid learning is sufficient and fulfilled